Hypermarkets‟ E-commerce Adoption among Youth in Puchong, Malaysia - Vaicondam, Yamunah; Subramaniam, Muthaloo; Aliyu, Mustapha (International Journal of Psychosocial Rehabilitation, 2020)
Businesses across the world are adopting e-commerce to reduce costs and serve customers better. Consequently, many “brick and mortar” businesses (physical stores) have changed to “click and mortar” businesses (both an online and a physical stores). Previous studies indicated that lack of adequate investments in ecommerce innovations have lagged the business transformation and growth and also on how youths are adopting ecommerce. Therefore, this study examines the factors affecting consumers’ adoption of e-commerce in Malaysian hypermarkets among youth. The dimensions used in this study are trust, service quality, time-saving, convenience and ease of use, to check the effect on consumer e-commerce adoption. In this study, the explanatory and descriptive research design were employed. The cross-sectional survey method employed using Likert scale questionnaire containing 30 questions. A sample of 229 respondents obtained using convenience sampling and later analyzed using SPSS by conducting descriptive statistics, correlation and regression analyses to examine the effect of the independent variable on e-commerce adoption. The findings indicated that service quality, timesaving, convenience and ease of use have a positive significant effect on e-commerce adoption among youth. Diffusion of innovation theory supports that trust is relevant for consumers to accept any innovation because youth are now easily adapting to more technology, its convenience and safe of time. Expectation disconfirmation theory explains the importance of service quality in meeting consumer expectation on new technologies and innovation.